Fire and water : a transdisciplinary investigation of water governance in the lower Sundays River Valley, South Africa - Clifford-Holmes, Jai Kumar (Rhodes University, Faculty of Science, Institute for Water Research, 2015)
The implementation of water policy and the integrated management of water face multiple challenges in South Africa (SA), despite the successes of post-apartheid government programmes in which some significant equity, sustainability and efficiency milestones have been met. This study uses a series of intervention processes into municipal water service delivery to explore the context, constraints, and real-world messiness in which local water authorities operate. The equitable provision of drinking water by local government and the collaborative management of untreated water by 'water user associations' are two sites of institutional conflict that have been subjected to broad 'turnaround' and 'transformation' attempts at the national level. This thesis seeks to explore and understand the use of transdisciplinary research in engaging local water authorities in a process of institutional change that increases the likelihood of equitable water supply in the Lower Sundays River Valley (LSRV). Fieldwork was conducted as part of a broader action research process involving the attempted 'turnaround' of the Sundays River Valley Municipality (SRVM) between 2011 and 2014. A multi-method research approach was employed, which drew on institutional, ethnographic, and systems analyses within an evolving, transdisciplinary methodology. In the single case study research design, qualitative and quantitative data were collected via participant observation, interviews and documentary sources. Analytical methods included system dynamics modelling and an adapted form of the ethnographic tool of 'thick description', which were linked in a governance analysis. Government interventions into the SRVM failed to take account of the systemic complexity of the municipal operating environment, the interactions of which are described in this study as the 'modes of failure' of local government. These modes included the perpetual 'firefighting' responses of municipal officials to crises, and the simultaneous underinvestment in, and over-extension of, water supply infrastructure, which is a rational approach to addressing current water shortages when funds are unavailable for maintenance, refurbishment, or the construction of new infrastructure. The over-burdening of municipalities with technocratic requirements, the presence of gaps in the institutional arrangements governing water supply in the LSRV, and the lack of coordination in government interventions are analysed in this study, with policy recommendations resulting. The primary contribution of this study is in providing a substantively-contextualised case study that illustrates the value of systemic, engaged, extended, and embedded transdisciplinary research.
Keywords: Lower Sundays River Valley Municipality (Eastern Cape, -- South Africa); Water -- Law and legislation -- South Africa; Water-supply -- Management; Municipal services -- South Africa -- Eastern Cape; Fire extinction -- South Africa -- Eastern Cape; Integrated water development -- South Africa -- Eastern Cape; Water quality management -- South Africa -- Eastern Cape; Water resources development -- South Africa -- Eastern Cape